Takhrij and Syarah Hadith of Chemistry: The Dangers of the Operation Plastick and Tattoo Ink in Islam and Science - Novianti, Fitria Listi; Yunus, Badruzzaman M. (Research Parks Publishing LLC, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad Saw. about the prohibition of getting tattooed. This research method is qualitative through the approach of takhrij and syarah hadith with chemical analysis. The results and discussion of this research is about the dangers of tattooing skin and plastic surgery because both processes use dangerous chemicals that can damage the body and are prohibited in Islam because they include activities that change Allah creation. The conclusion of this research is takhrij and syarah hadith of the Prophet Muhammad Saw. about the prohibition of being tattooed with chemical analysis which is a trend in the era of modern people's lifestyle.